P388 Analysis of the impact of body mass index on efficacy and safety in the tofacitinib OCTAVE ulcerative colitis programme. (25th January 2019) - Farraye, F A; Qazi, T; Kotze, P G; Moore, G T; Kayhan, C; Mundayat, R; Maller, E; Su, C; Soonasra, A
Abstract: Background: High body mass index (BMI) can be associated with increased risk of treatment failure in biologic-treated patients with ulcerative colitis (UC). 1 Tofacitinib is an oral, small-molecule JAK inhibitor approved in several countries for the treatment of UC. We present analysis of BMI effect on tofacitinib efficacy and safety in the tofacitinib UC clinical programme. Methods: Data from two identical, 8-week (week) induction studies (OCTAVE Induction 1 and 2, NCT01465763 and NCT01458951) 2 and a 52-week maintenance study (OCTAVE Sustain, NCT01458574) 2 were analysed. Patients received placebo, tofacitinib 5 or 10 mg twice daily (BID). Patients were stratified by BMI <25, 25–<30 or ≥30 for analysis at Week 8 (Induction 1 and 2) and Week 52 (Sustain) for efficacy endpoints remission, clinical response and mucosal healing (MH), and for safety outcomes including infections. Results: Patient demographics and baseline characteristics were similar for placebo and tofacitinib groups. The majority of patients in each group had BMI <25 (table). In Induction 1 and 2 and Sustain, tofacitinib-treated patients had a gradual increase in body weight and BMI over time vs. placebo. In Induction 1 and 2, for tofacitinib 10 mg BID at Week 8, patients with BMI <25 had numerically higher proportions of remission vs. other BMI groups. Proportion of patients with MH was lower in BMI ≥30. Clinical response was similar in all BMI groups. At Sustain Week 52, for tofacitinib 5 mg BID, BMI 25–<30 had highest proportions of remission and MH; BMI ≥30 had highest proportion of sustained steroid-free remission and lowest proportion for MH and clinical response vs. other BMI groups. Clinical response was similar for all BMI groups. In Sustain, for tofacitinib 10 mg BID, BMI ≥30 had highest proportions of remission, sustained steroid-free remission, MH, and clinical response. For tofacitinib patients in Induction 1 and 2, opportunistic infections (OI) were rare; proportions were similar across BMI groups. BMI stratification for infections and serious infections (SI) was not available. In Sustain, for tofacitinib 5 and 10 mg BID, infections were numerically higher for BMI 25–<30 vs. others. There were few OI or SI, and proportions were similar among subgroups. Conclusions: The majority of patients with UC in the OCTAVE programme had BMI <25. In subgroup analyses by BMI, patients with high BMI receiving tofacitinib did not demonstrate lower efficacy endpoints or greater infection rates. However, limitations include low patient numbers in the BMI ≥30 group and rare OI/SI events. References 1. Kurnool S, Nguyen NH, Proudfoot J, et al. High body mass index is associated with increased risk of treatment failure and surgery in biologic-treated patients with ulcerative colitis. Aliment Pharmacol Ther 2018;47:1472–9. doi:10.1111/apt.14665 2. Sandborn WJ, Su C, Sands BE, et al. Tofacitinib as induction and maintenance therapy for ulcerative colitis. N Engl J Med 2017;376:1723–36. doi:10.1056/NEJMoa1606910